2012
DOI: 10.1038/ejhg.2012.180
|View full text |Cite
|
Sign up to set email alerts
|

Newborn screening for cystic fibrosis: Polish 4 years’ experience with CFTR sequencing strategy

Abstract: Newborn screening for cystic fibrosis (NBS CF) in Poland was started in September 2006. Summary from 4 years' experience is presented in this study. The immunoreactive trypsin/DNA sequencing strategy was implemented. The group of 1 212 487 newborns were screened for cystic fibrosis during the programme. We identified a total of 221 CF cases during this period, including, 4 CF cases were reported to be omitted by NBS CF. Disease incidence in Poland based on the programme results was estimated as 1/4394 and carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 28 publications
0
33
1
2
Order By: Relevance
“…Beyond Ireland which has the highest incidence of CF in Europe (1:1353) [39], the incidence ranges from 1:2800 in the UK [38] to 1:10,000 in Russia [40] ( Figure 5). It is 1:2850 in Belgium [41], about 1:4500 in France [42], Germany [14], Italy [38,43,44], and Spain (where large regional variations are observed) [45], while it oscillates between 1:5200 and 1:6500 in Central Europe (Czech Republic [32], Denmark [46], Netherlands [47], Poland [48], Slovakia [49], and Sweden [50]). The incidence appears lower than 1:7000 in three European countries (Portugal [51], Norway [52], and Russia [40]) as well as in various regions of Spain [45].…”
Section: Europementioning
confidence: 99%
“…Beyond Ireland which has the highest incidence of CF in Europe (1:1353) [39], the incidence ranges from 1:2800 in the UK [38] to 1:10,000 in Russia [40] ( Figure 5). It is 1:2850 in Belgium [41], about 1:4500 in France [42], Germany [14], Italy [38,43,44], and Spain (where large regional variations are observed) [45], while it oscillates between 1:5200 and 1:6500 in Central Europe (Czech Republic [32], Denmark [46], Netherlands [47], Poland [48], Slovakia [49], and Sweden [50]). The incidence appears lower than 1:7000 in three European countries (Portugal [51], Norway [52], and Russia [40]) as well as in various regions of Spain [45].…”
Section: Europementioning
confidence: 99%
“…It significantly shortens the survival time of patients. In Poland, it occurs in 1 per 4394 newborns 1 . Over recent decades the patients' life has extended, mainly thanks to integrated, multidisciplinary care.…”
Section: Introductionmentioning
confidence: 99%
“…It was identified in one case out of 56 in a study of children with CF from North‐West of Iran . In another study of more than 7000 newborns with positive CF‐NBS, L467F was found in one baby with immunoreactive trypsinogen >99.4 percentile and no symptoms of CF. These data suggest that L467F could be a rare polymorphism or acts as a variant with very mild effect on gene/protein function.…”
Section: Lessons Learnedmentioning
confidence: 94%